2011
DOI: 10.2190/ec.45.3.d
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Preservice Teachers' Technology-Related Abilities, Beliefs, and Intentions to Use Technology in Their Future Classrooms

Abstract: This study investigated relationships among students' technology-related abilities, beliefs, and intentions. Participants were 217 preservice teachers who responded to post-course surveys. Value beliefs were the best predictor of their intentions to use a variety of software and their intentions regarding frequency of technology use with students in their future classrooms. Selfefficacy for technology integration also contributed to the prediction of intentions to use a variety of software, and technological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 25 publications
8
66
0
7
Order By: Relevance
“…Besides sufficient technology education, some research revealed that value beliefs are the best predictor of pre-service teachers' intentions to use a variety of software and their intentions regarding frequency of technology use with students in their future classrooms [11,12]. Technology knowledge is unlikely to be used unless teachers can conceive of technology uses that are consistent with their existing pedagogical beliefs [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides sufficient technology education, some research revealed that value beliefs are the best predictor of pre-service teachers' intentions to use a variety of software and their intentions regarding frequency of technology use with students in their future classrooms [11,12]. Technology knowledge is unlikely to be used unless teachers can conceive of technology uses that are consistent with their existing pedagogical beliefs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Technology knowledge is unlikely to be used unless teachers can conceive of technology uses that are consistent with their existing pedagogical beliefs [13]. Perceptions of the importance or relevancy of a task for the accomplishment of future goals significantly influenced pre-service teachers' intentions of technology use [11]. It became clear that simply increasing computer access was not sufficient to change teachers' technology practices, especially if this increased access was not accompanied by a corresponding shift in teachers' pedagogical beliefs [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…At this point, it is crucial to analyze the teachers' computer anxiety levels and self-efficacy beliefs. Upon analyzing the literature, it is seen that teachers' anxiety levels decrease as their computer self-efficacy increase and they tend to use technology more in their classes (Niederhauser and Perkmen, 2010;Anderson et al, 2011;Liu, 2011). Within this context, teachers' computer anxiety levels and selfefficacies are two different variances that should be considered to enable them to use computer and education technologies more efficiently and effectively in their education and training activities.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, teachers with higher self-efficacy have displayed more positive attitudes towards technology integration into classrooms (Anderson, Groulx, & Maninger, 2011). Wang, Ertmer, and Newby (2004) reported that although "enhanced self-efficacy beliefs do not automatically translate into the actual use of technology among teachers, they are a necessary for technology integration" (p. 242).…”
Section: Resultsmentioning
confidence: 99%
“…In a U.S. based national survey, Anderson et al (2011) found that "the majority of school district administrators (60%) and principals (55%) reported that effective integration of instructional technology was extremely important to their core mission, whereas only 38% of teachers and future teachers reported similar views" (p. 321). The results of the current study highlight the need for continued exploration into several areas.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%